From steel to slots : casino capitalism in the postindustrial city - Taft, Chloe E. (Harvard University Press, 2016)
"Bethlehem, Pennsylvania, the world headquarters of the Bethlehem Steel Corporation for most of the twentieth century, is now home to an industrial-themed casino. Based on extensive fieldwork and dozens of interviews, From Steel to Slots explores how the global transitions of "casino capitalism" and a shift towards economies based on service, entertainment, and financial speculation are lived, legitimated, and contested in and through the local landscape of a former industrial city. As legalized gambling spreads in the United States and around the world to drive economic revitalization, create jobs, and generate tax revenues, multinational casino corporations are increasingly acting as urban planners."--Provided by publisher.